Dominant woody species, their distribution and threat in Ambrolauri, Georgia - Tamar Khardzhiani; Roman Maisuradze (Journal of Forest Science, 2020)
The paper presents the maps of ecosystems and 11 dominant woody species of Ambrolauri municipality, Georgia (Europe). Forest cover comprises approximately 68% of the study area, most of which are natural forests. Almost all formations of natural forests, depicted on the Georgian section of the Map of the Natural Vegetation of Europe, are still preserved in the research area. Nearly 40% of the forested land is broadleaf forest. Woody species are better preserved in the upper reaches of rivers, while an anthropogenic transformation is most visible in the Lower Racha Floodplain. A majority of the species discussed in the paper are included in the IUCN Red List of Threatened Species. The paper also deals with the issues of forest land degradation and threats imposed by invasive species to biodiversity.